How Does Self-Concept Differentiation Work in Chinese Retirees: A Moderated Mediation Analysis - Zhu, Changzheng; Zhu, Min; Gao, Xiangping; Liu, Xiaoshi (Frontiers in Psychology, 2021)
Self-concept differentiation (SCD) is a sign of fragmentation of the self rather than specialization of role identities for it’s robust relationship with psychological adjustment, however, the study of the underlying mechanism for this relationship between SCD and psychological adjustment is not sufficient. The current study examined the SCD-psychological adjustment (psychological well-being, depression, and anxiety) relationship in a sample of 158 Chinese retirees (55 to 92 years, M = 71.12, SD = 9.13) to explore whether it is mediated by Self-consistency and Congruence (SCC) and moderated by age. It was found that SCC partially mediated relations between SCD and indices of psychological adjustment, and age moderated this mediation effect. The mediation effects were found in mean and high age participants, but not in low age participants. Our findings indicate that, in different age stages, the internal mechanism of SCD affecting psychological adaptation was not the same, and a low-differentiated or highly integrated self can be served as an adaptive resources to maintain the elderly high subjective well-being and protect them from anxiety and depression.